2011 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2011
DOI: 10.1109/iembs.2011.6090743
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical & experimental analysis of the Non Markov Parameter to detect low frequency synchronisation in time series analysis

Abstract: A theoretical investigation into the behaviour of the Non-Markov Parameter is performed from a signal processing perspective in contrast to previous methodologies based on stochastic processes theory. The results indicate that the NMP can be regarded as an informational metric which is indicative of the degree of low frequency synchronisation in a complex system. These results have deep implications for physiological analysis of biological systems where the presence of sychronisation is often a marker of patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Complex measures have been used to look at MERs, and it has been shown that some techniques, such as the Non-Markov parameter (NMP) relate to the PSD (Varghese, et al, 2011).…”
Section: Procedures For Comparison Of Numerical and Experimental Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Complex measures have been used to look at MERs, and it has been shown that some techniques, such as the Non-Markov parameter (NMP) relate to the PSD (Varghese, et al, 2011).…”
Section: Procedures For Comparison Of Numerical and Experimental Resultsmentioning
confidence: 99%
“…Recent work has shown that with the correct measure, correlations between MER recordings and patient response to symantic tests has been demonstrated (P. A. Paul A. Meehan et al, 2011;Varghese et al, 2011).…”
Section: Suggestions For Further Researchmentioning
confidence: 99%
“…structure, which has a non zero λ value, was considered in [115]. A full derivation of the functional form of this λ n relaxation parameters is provided in section A.1.…”
Section: Mori-zwanzig Kinetic Equationsmentioning
confidence: 99%
“…These results suggest that signal metrics to differentiate complex systems can be developed by analysing different properties of the measured power spectrum. The previous success of the NMP [67], [106], [111], [112], [115] helps elucidate specifically what properties (spectral spread and DC offset) should be explored, but does not necessarily require Mori-Zwanzig theory to interpret the results.…”
Section: Analysis Of the Non-markov Parametersmentioning
confidence: 99%
See 1 more Smart Citation